2013
DOI: 10.5171/2013.290047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multidrug-Resistant Pseudomonas aeruginosa in Patients with Nosocomial Infections at a University Hospital in Egypt, with Special Reference to Typing Methods

Abstract: Multidrug resistant (MDR) P.aeruginosa had emerged in Egypt and seen mainly in nosocomial infections due to the selective pressure by overusage of antibiotics. This study was planned to delineate prevalence of MDR P.aeruginosa in nosocomial infection patients, and to screen for ESβLs producing P.aeruginosa with typing of P.aeruginosa isolates in Menofia University Hospitals (MUH), Egypt. Our study included 287 inpatients admitted to Menoufia University Hospital and having different nosocomial infections. Sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
56
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 6 publications
22
56
6
1
Order By: Relevance
“…This study showed that nosocomial P. aeruginosa clinical isolates was recovered from tested clinical specimens at a rate of16.2 %. This is in agreement with Gad et al, 2007 andMahmoud et al, 2013 who reported rate of 18% and 19% respectively.…”
Section: Resultssupporting
confidence: 82%
“…This study showed that nosocomial P. aeruginosa clinical isolates was recovered from tested clinical specimens at a rate of16.2 %. This is in agreement with Gad et al, 2007 andMahmoud et al, 2013 who reported rate of 18% and 19% respectively.…”
Section: Resultssupporting
confidence: 82%
“…A recent study from India has also reported a good efficacy of amikacin against P. aeruginosa, with <6% of unsusceptibility, placing the drug as the most effective one to kill the bacteria among others tested [4]. However, the efficacy of this drug is reportedly lower when tested to samples from nosocomial infections, 80%, as stated by another study from Egypt [23].…”
Section: Discussionmentioning
confidence: 76%
“…These hospitals are tertiary hospitals with expected high rates of complicated cases due to receiving difficult cases from all over the country. Similarly 19% P. aeruginosa were reported as causes of HAIs in Menofia Hospital University, Egypt with 9.5% of the isolated P. aeruginosa are corded as MDR [11]. A figure of 18% was recorded by Gad in Minia hospitals in Egypt [12].…”
Section: Discussionmentioning
confidence: 92%
“…In India, the resistance rate of P. aeruginosa to ceftazidime was 53% [15]. A much higher rate of ceftazidime resistant P. aeruginosa, (91%) was detected in another part of Egypt [11]. Thus, it is evident that high rates of ceftazidime resistance in P. aeruginosa are detected in different areas of Egypt.…”
Section: Discussionmentioning
confidence: 95%